Assédio Moral (e/ou Sexual) no trabalho - Bandeira, Gonçalo S. de Melo (2017)
Publicámos um artigo em 2011 na Revista de Estudios Penales Y Criminológicos da Universidade de Santiago de Compostela, sobre assédio moral: “Poderá ser a Criminalização do Assédio Moral e/ou mobbing, rectius no trabalho, respeitadora dos princípios constitucionais da necessidade, adequação, proporcionalidade e intervenção mínima penais? - A Lesão dos Direitos Fundamentais Constitucionais dos trabalhadores: o caso português”. Está livremente acessível pela internet.e: http://www.usc.es/revistas/index.php/epc/article/view/144 § We published an article in 2011 in the Journal of Criminal and Criminological Studies of the University of Santiago de Compostela on moral harassment: "It could be the criminalization of moral harassment and / or mobbing, rectius at work, respecting the constitutional principles of necessity, adequacy, proportionality and minimal criminal intervention? - The Injury of Fundamental Constitutional Rights of Workers: The Portuguese Case ". It is freely accessible on the internet.e: http://www.usc.es/revistas/index.php/epc/article/view/144